Editorial - Economy and Culture - Vesna Vučinić Nešković (Etnoantropološki Problemi, 2022)
The studies presented in this volume of Issues in Ethnology and Anthropology came into being as a result of research within the project entitled Eastern Enlargement - Western Enlargement: Cultural Encounters in the European Economy and Society after the Accession, otherwise known as Project Dioscuri.